Nutritional Immunity Triggers the Modulation of Iron Metabolism Genes in the Sub-Antarctic Notothenioid Eleginops maclovinus in Response to Piscirickettsia salmonis - Martínez, Danixa; Oyarzún, Ricardo; Pontigo, Juan Pablo; Romero, Alex; Yáñez, Alejandro J.; Vargas-Chacoff, Luis (Frontiers in Immunology, 2017)
Iron deprivation is a nutritional immunity mechanism through which fish can limit the amount of iron available to invading bacteria. The aim of this study was to evaluate the modulation of iron metabolism genes in the liver and brain of sub-Antarctic Notothenioid Eleginops maclovinus challenged with Piscirickettsia salmonis. The specimens were inoculated with two P. salmonis strains: LF-89 (ATCC® VR-1361™) and Austral-005 (antibiotic resistant). Hepatic and brain samples were collected at intervals over a period of 35 days. Gene expression (by RT-qPCR) of proteins involved in iron storage, transport, and binding were statistically modulated in infected fish as compared to control counterparts. Specifically, the expression profiles of the transferrin and hemopexin genes in the liver, as well as the expression profiles of ferritin-M, ferritin-L, and transferrin in the brain, were similar for both experimental groups. Nevertheless, the remaining genes such as ferritin-H, ceruloplasmin, hepcidin, and haptoglobin presented tissue-specific expression profiles that varied in relation to the injected bacterial strain and sampling time-point. These results suggest that nutritional immunity could be an important immune defense mechanism for E. maclovinus against P. salmonis injection. This study provides relevant information for understanding iron metabolism of a sub-Antarctic Notothenioid fish.